Work-family enrichment among parent nurses: a cross-sectional scale development and validation study - Toshimi Kawakita; Yasuko Hosoda (BMC, 2024)
Abstract Background Work-family enrichment refers to the extent to which experiences in one role improve the quality of life in another role, and the bidirectionality indicates that benefits derived from work can be applied to family and vice versa. Parent nurses, that is, female nurses who are raising preschool children, play a major role at work and in the family. Thus, work-family enrichment is significant for them. The Work-Family Enrichment Scale cannot be generalized to parent nurses. This study was aimed at developing and psychometrically validating a draft Work-Family Enrichment Scale for Parent Nurses. Methods A questionnaire survey was conducted among 1,090 parent nurses who were randomly sampled from hospitals with more than 200 beds in Japan. The survey evaluated (1) a draft Work-Family Enrichment Scale for Parent Nurses, (2) the Japanese version of the Work-Family Enrichment Scale, and (3) the Positive Spillover Scale. The scales were psychometrically evaluated for internal consistency, construct validity, and criterion-related validity. Results Data from 503 participants (age, mean ± standard deviation [range] 35.5 ± 4.96 [23-47] years) were analyzed. Results of exploratory factor analysis, the work to family enrichment direction yielded five factors for 23 items: "emotional fulfillment," "efficiency," "ability to lead," "displaying industriousness," and "self-growth." Cronbach's alpha coefficients ranged from 0.862 to 0.914. In the family-to-work enrichment direction, there were five factors for 28 items: "help-seeking," "receptiveness," "expansion of one's horizon," "efficiency," and "emotional fulfillment." Cronbach's alpha coefficients ranged from 0.790 to 0.907. Additionally, the correlation coefficients reporting criterion-related validity were 0.685 and 0.619 with regard to the Japanese version of the Work-Family Enrichment Scale and 0.596 and 0.534 with the Positive Spillover Scale for the Work-to-Family Enrichment Scale and the Family-to-Work Enrichment Scale for Parent Nurses, respectively. Conclusions The Work-Family Enrichment Scale for Parent Nurses has adequate reliability and validity and can be used as an effective measure to assess the positive aspects of work and family roles among female parent nurses.